Assessment of psychological alarms and coping strategies of medical students with irritable bowel syndrome at Zagazig University: A cross-sectional study - Noha O. Frere; Al Zahraa M. Soliman; Hussein M. Salama; Mohamed O. Wahba; Walaa S. Fouad (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Irritable bowel syndrome (IBS) is one of the most prevalent functional gastrointestinal disorders. Medical students tend to report a higher prevalence of IBS since they are under constant stress. Many psychological difficulties are associated with IBS. To cope with IBS, individuals use various strategies which can impact the intensification or alleviation of IBS symptoms. The objective of this study was to assess the prevalence of IBS in medical students as well as psychological alarms and coping strategie employed by IBS sufferers. MATERIALS AND METHODS: We conducted a cross-sectional study from December 2022 to February 2023. Study participants were first to fifth year medical school students at Zagazig University, Egypt. Data were collected using a structured questionnaire comprising four sections: sociodemographic and clinical data; Rome IV criteria for the diagnosis of IBS; the alarm questionnaire for functional gastrointestinal disorders; and the Coping Strategies Questionnaire (CSQ24). Chi-square test or Fischer's exact test, as appropriate, were used to test for association. Binary logistic regression with a backward stepwise method was used to determine significant risk factors of negative coping with IBS. RESULTS: Of the studied 221 medical students, 38% had IBS. A statistically significant association was observed between IBS and the feeling of tension, anxiety, nervousness, depression, and frustration in the previous week, severe pain in the past 4 weeks, and the feeling that the bad situation would not get any better. Most of the students in the IBS group coped positively with stress, while 19.0% were negative in coping. Pain affecting the daily activities and the feelings of depression and frustration to the point of self-harm or suicide were the most significant correlates of IBS group's inability to cope. CONCLUSION: The prevalence of IBS in medical students at Zagazig University was 38%. We recommend psychological intervention and stress management programs to help medical students cope with IBS.